A single-stage direct-conversion AC-DC converter for inductively powered application - Low, Qiong Wei (2019)
An innovative single-stage ac-dc converter for low power, low frequency skin depth wireless power transfer is presented. The power conversion efficiency (PCE) of a wireless power receiver is limited by the cascaded two-stage design, which constitutes a rectifier and a voltage regulator. Owing to the proposed ON-/OFF-mode regulating rectifier, the voltage rectification and regulation are achieved simultaneously in one stage, thereby improving the PCE substantially. The output voltage regulation is accomplished by incorporating the pulse skipping modulation and the pulse frequency modulation control into the structure. In addition, there is no bulky inductor utilized in the proposed one-stage design. Therefore, the footprint and cost of the receiver can be minimized effectively. The proposed design has been fabricated in 0.18-μm standard CMOS process. Measurement results show that a peak power transfer efficiency of 93.48% is achieved at a regulated output voltage of 2 V in an output power range of 2-80 mW.